Comparison of 18F-FDG PET/CT and ceCT Results in the Assessment of RCC Recurrence - Elgin OZKAN; Mine ARAZ; Cigdem SOYDAL; Gulseren ARAS (Studies on Stem Cells Research and Therapy - Peertechz Publications, 2016)
Aim: To compare the results of fl uorine-18 (¹8F) fl uorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) and contrast enhanced computed tomography (ceCT) in the assessment of renal cell carcinoma (RCC) recurrences when ceCT had suspected lesions for local recurrence and/or distant metastases. Methods: A total of 22 patients (14 Male, 8 Female; mean age: 59±9 years) who were referred to perform 18F-FDG PET/CT for restaging of RCC were included in this study. All patients had suspected lesions in thoracal and/or abdominal ceCT for local recurrence and/or distant metastases before PET/CT. A retrospective analysis of the ¹8F-FDG PET/CT results was compared with ceCT results. The compatibility  ratios were calculated and accuracy of the 18F-FDG PET/CT was determined. Aggrement between 18F- FDG PET/CT and ceCT was calculated using kappa statistics. Results: The overall concordance rate between the two imaging modalities was 32% (7/22 patients).The rate of concordance for local recurrence was 86% (Kappa:0.67), and for distant metastases was 68%  (Kappa:0.40). Distant metastases were also separately investigated and the two imaging methods showed a concordance of 86% (Kappa:0.70) for distant lymph node, 86% (Kappa:0.67) for lung, 91%  (Kappa:0.64) for liver and 86% (Kappa:0.33) for bone and 95% for spleen. Conclusion: 18F-FDG PET/CT is not enough alone in the detection of local recurrence and distant metastases of RCC. On the other hand, evaluation of 18F-FDG PET/CT and ceCT together signifi cantly improves the detection of RCC recurrence. A negative 18F-FDG PET/CT may contribute to exclusion of  suspected metastatic lesions, unless they are milimetric.